Diagnosis and treatment of Helicobacter pylori infection by physicians in China: A nationwide cross‐sectional study. Issue 3 (1st April 2022) - Song, Zhiqiang; Chen, Ye; Lu, Hong; Zeng, Zhirong; Wang, Weihong; Liu, Xiaofeng; Zhang, Guoxin; Du, Qin; Xia, Xingzhou; Li, Changping; Jiang, Shulin; Wu, Ting; et al.
Abstract: Background: To investigate the current state of knowledge and practice of Helicobacter pylori ( H .  pylori ) infection management in China. Materials and Methods: This nationwide, multicenter, cross‐sectional questionnaire survey was conducted between March and April 2021 with respect to the diagnosis and treatment of H .  pylori infection in 31 provinces, encompassing over 1000 hospitals in mainland China. General physician information, diagnostic and detection status, eradication treatment, reexamination and follow‐up after treatment, and basic knowledge of physicians were collected and compared with the Fifth Chinese National Consensus Report on Management of H .  pylori infection and the 2016 Maastricht V/Florence guidelines. The subgroup analysis was also performed. Results: Of the 6873 questionnaire respondents, 48.8% were males, and 51.2% were females. Approximately, 26.5% of respondents indicated that their hospitals had dedicated clinics for managing H .  pylori infection. Moreover, 88.0% of respondents prescribed a bismuth‐containing quadruple regimen as the initial eradication treatment, and 92.7% deemed the gastric acid suppression critical. Furthermore, 91.0% of respondents routinely recommended a reexamination 1–2 months after eradication therapy, and 95.1% advised patients to stop PPI treatment at least 2 weeks before reexamination. The detail of following (the choice of target population/methods; the choice/availability of drugs/regimens, indications for eradication, factors influencing eradication efficacy/improvement methods and factors influencing adherence, management options/factors influencing relapse; the timing and methods, awareness of reinfection rates/prevention measures, and the approach to continuing education, awareness of guidelines, and acceptance of current core concepts of management) was also described. Subgroup analysis further revealed that significant differences were existed in being gastroenterologist or not, different education level, professional title, years of working, and provincial administrative regions. Conclusions: Chinese physicians' skills and knowledge about the diagnosis and treatment of H .  pylori infection could be improved. More works on education are needed in future.